The role of microfinance bank on the SMEs performance in Nigeria - Mahat, Fauziah; Zannah, Mohammed (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Previous studies on the role of microfinance institutions in small and medium enterprises (SMEs) performance findings were inconsistent to one another, some found the significant impact of microfinance while other results show negative impacts. This study will assess the impact of microfinance in northeastern Nigeria. A structured questionnaire was used to gather the data, random sampling method was also adopted in surveying the 309 number of the respondent. The finding shows a significant relationship between microfinance loan and small and medium performance, the relationship is medium and positive. Moreover, there is the impact of microfinance on small and medium enterprises performance. The loan has highly increased the performance. The study also recommends the government to consider and increase the number of a microfinance institution in the zone and formulate a law for small and medium enterprises to access loan in commercial banks. A chart were also included to show the level of awareness of the microfinance bank in the country.